Optimal Volt-VAr Control Operation for Finergy Cost Reduction in Distribution Systems Considering a Voltage Dependent Load Model - Antunez, Carlos Sabillon [UNESP]; Melgar Dominguez, Ozy D. [UNESP]; Franco, John P. [UNESP]; Lavorato, Marina; Rider, Marcos J.; IEEE (Ieee, 2016)
In this paper, a new mixed integer linear programming formulation is proposed to optimally control the Volt-VAr control devices installed in a balanced electrical distribution system (EDS), taking into account the presence of dispatchable distributed generation (DG) units. The formulation considers a voltage dependent load model and aims to reduce the cost of the energy purchased to the substation and DG units on a daylong time period. The proposed method defines the settings for the voltage regulators, on-load tap changer, capacitors, and DG units. The presented formulation was tested in a 42-node EDS and the obtained results prove that the methodology enhances the EDS economic operation with a very low computational effort.
Keywords: Energy cost reduction; mixed integer linear programming; volt-var control operation; voltage dependent load model